PENAMBAHAN KOSAKATA DAN PENINGKATAN NILAI KEHIDUPAN PADA ANAK TUNARUNGU MELALUI MUSIKALISASI PUISI - Munika, Sinta; Nasriah, Sri; Dyah, Luthfi; A, Ubaidurrosyid (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The student creativity program in community services is aimed at using musical poems as the media to improve the vocabularies of deaf children and internalizing moral values into them. The methods are lecturing, demonstration, practice and performance. The performance of musical poems is to build children’s self confidence. The activities took four months for the program preparation, implementation and then evaluation. The program is carried out among six students of Widya Mulia Special School, Pundong, Bantul, Yogyakarta. The use of musical poem is found to improve the vocabularies of deaf children. It is shown in their written and spoken communication. Besides, the children are able to enact moral values such as religiousity, confidence, autonomy, discipline and honesty. Musical poems are suitable to be implemented among deaf children based on their level of hearing ability. Therefore, the program successfully solves the deaf children’ problems in language learning. It is recommended that teachers in the school implement the program for developing deaf children’s language skills. The children are also able to share knowledge and experiences to others for a better life.